2017
DOI: 10.1063/1.4976895
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of green infrastructure concept in Citarum Watershed

Abstract: Abstract. Green infrastructure has several benefits compared to grey infrastructure in term of environmental services and sustainability, such as reducing energy consumption, improving air quality, providing carbon sequestration, and increasing property values. Nevertheless in practice, the implementation of the concept in Indonesia is still limited. Implementation of the certain concept has to be guided in planning document. In this paper, green infrastructure concept in the current spatial plan and other pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Intrinsic or extrinsic motivational factors such as incentives and rebate programs have been found to influence people's behavior and attitude (Herzberg et al, 2011). Maryati and Humaira (2017) found that lack of incentives and disincentives was the main obstacle to introducing SSM in Indonesia and Rowe et al (2016) concluded that financial incentives/disincentives might be the best way to encourage SSM in New Jersey. “Aesthetics” also gained a low rank, which is noteworthy because aesthetics has been found to be an important benefit of SSM as it can provide sociocultural, economic, and environmental benefits to communities (Haruna et al, 2018; Vojinovic et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Intrinsic or extrinsic motivational factors such as incentives and rebate programs have been found to influence people's behavior and attitude (Herzberg et al, 2011). Maryati and Humaira (2017) found that lack of incentives and disincentives was the main obstacle to introducing SSM in Indonesia and Rowe et al (2016) concluded that financial incentives/disincentives might be the best way to encourage SSM in New Jersey. “Aesthetics” also gained a low rank, which is noteworthy because aesthetics has been found to be an important benefit of SSM as it can provide sociocultural, economic, and environmental benefits to communities (Haruna et al, 2018; Vojinovic et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…This integration implies a shift in institutional and organisational arrangements to reflect the required interdisciplinary collaboration, which is not the case for conventional public sector organisational arrangements known to fragment and segregate development issues and manage them discretely (Lennon et al 2017). Additionally, the lack of city or area enforcement and the lack of monitoring in implementing their greening strategies are considered major hindrances (Maryati and Humaira 2016).…”
Section: Mainstreaming Urban Greening In City Policies and Strategiesmentioning
confidence: 99%
“…Green roofs help reduce stormwater volume and pollution but have a limited effect on peak flows. • Many implementation in particular in Thailand, Malaysia, Singapore and Indonesia (Lim and Lu 2016;Maryati and Humaira 2017).…”
Section: Green Roofs (12%)mentioning
confidence: 99%
“…• Features for floodwater diversion are common in Southeast Asia, including urban water bodies (Maryati and Humaira 2017;Wolf et al 2020) and furrows (Watkin et al 2019).…”
Section: Wetlands (41%)mentioning
confidence: 99%